KINERJA IMPLEMENTASI KEBIJAKAN PROGRAM KARTU PRAKERJA DI TENGAH PANDEMI COVID-19 DI KOTA JAKARTA TIMUR - Tritanti Tritanti; Budi Puspo Priyadi; Hartuti Purnaweni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
This research is motivated by employment problems, namely the high level of young people who are working or not working who lack competence, the occurrence ofskill gap, low productivity which results in losing competitiveness with foreign workers. The government's efforts to overcome these employment problems are by issuing a Pre-Employment Card program policy. The program was carried out when the Covid-19 pandemic caused the program to have other objectives, namely associal safety net. This caused the budget for the program to double. During its implementation, the Pre-Employment Card program drew a lot of criticism from the public, politicians and observers and even the program participants themselves who stated that the program was not on target and was not effective in helping the community during a pandemic, especially in increasing competency. Several program participants who live in East Jakarta City expressed the same thing. The purpose of this research is to find out the performance of the implementation of the Pre-Employment Card program in the midst of the Covid-19 pandemic in the City of East Jakarta which has not been maximized; as well as knowing the obstacles to the non-maximum implementation of the PreEmployment Card program in East Jakarta City seen from the background of the social and economic conditions of the program participants. This study uses a descriptive qualitative method with an approachpurposive sampling and Netnography as the data collection method. The results of the study showed that the standards and objectives of the Pre-Employment Card program were in accordance with the recipients of the Pre-Employment Card program which were right on target but found defects in the process of using the program by participants who were also influenced by the program, but indeed the program objectives had not been achieved properly, apart from that financial resources had been fulfilled but there are indications of inaccuracy target. Factors from the social, economic and occupational background of the participants during the pandemic also contributed to the program's ineffectiveness towards the participants. Obstacles found related to increasing participant competence were influenced by the high price of training, the quality of the training material content, and the need for internet quota. The recommendations given are that the government is reviewing the program regarding dual roles, immediately implementing job training on a regular basisoffline coordinating with DKI Jakarta Manpower Office, East Jakarta City Sudinasker and BLK in East Jakarta City as well as evaluating partnerships with training providers.